Inequities in safe abortion: women’s care trajectories in Abuja and Lagos, Nigeria - Matthea Roemer; Boniface Ayanbekongshie Ushie; Akinsewa Akiode; Ogechi Onuoha; Ochanya Idoko; Anne Taiwo (BMC Public Health)
Abstract Background Unsafe abortion remains a significant cause of maternal morbidity and mortality in many African countries, including Nigeria. This study aims to fill gaps in understanding of how abortion safety has evolved since previous estimates. The study also offers new insight on pregnant people’s experiences along the abortion care trajectory and how sociodemographic factors correlate with these experiences and the overall safety of abortion. Methods Data presented are drawn from a larger study that was conducted in Lagos and Abuja, Nigeria in 2023 using a total market assessment approach. This analysis drew exclusively on data from a quantitative survey of women of reproductive age with a 5-year history of induced abortion(s). Abortion safety was operationalised based on two dimensions in line with a previous analysis of population-based survey data from Nigeria: [1] whether the method(s) used included any non-recommended methods and [2] whether the source(s) used were clinical or non-clinical. We combined source and method information to categorize a woman’s abortion into one of four safety categories. Analyses include frequencies of abortion safety and experiences along the abortion care trajectory, as well as bivariate and multivariate assessments of sociodemographic and reproductive history correlates. Results Two hundred women completed the survey of which 197 reported their abortion method and were included in this analysis. Almost half (44.7%) of respondents’ reported abortions were categorised as most unsafe involving non-recommended methods and non-clinical source(s). Those living in rural areas and those living in severe poverty were significantly more likely to have had the most unsafe abortions. Those living in poverty were also at increased likelihood of being unable to access an abortion from their preferred source and of experiencing any complications. Conclusion These findings confirm that unsafe abortion in Nigeria is a public health concern and an issue of social inequity. Efforts to improve equitable access to safe, high-quality and client-centred services are needed. National health policies must address both the legal and practical barriers to safe abortion access. Ensuring expanded access to in-facility surgical procedures and post-abortion care is critical for management of complications from continued unsafe abortion. Simultaneously, harm reduction efforts - including increasing awareness of quality medication abortion drugs for safer self-induction and training lower-cadre providers on the medical management of abortion - can help mitigate the toll of abortion-related morbidity and mortality.